MOTION RELIABILITY ANALYSIS OF A 6⁃DOF INDUSTRIAL ROBOT - LI ZiYi; DING Li; MA Rui; DUAN JinJun (Jixie qiangdu)
In order to evaluate the reliability and accuracy of the end⁃effector of a six⁃degree⁃of⁃freedom industrial robot in the task space,a robot motion reliability analysis strategy based on the envelope method was proposed.Firstly,the error function and reliability model of the robot system was obtained through kinematics.Secondly,the envelope method was used to solve the reliability model to obtain the failure probability of the end⁃effector,and the error function was linearized by Taylor′s formula,while redundant points in the covariance matrix were excluded in the calculation process to make it conform to the positive definite condition and improve the accuracy of the envelope.Finally,the proposed method was simulated and analyzed.The results show that the error of the envelope method compared with the Monte Carlo method is 0.5%~19.8%,which verifies the effectiveness of the method.